Project Based Learning untuk Meningkatkan Hasil Belajar Kimia Siswa Pokok Bahasan Hakikat Ilmu Kimia - Sasmono, Sasmono (JIPVA (Jurnal Pendidikan IPA Veteran), 2018)
The purpose of this study was to determine whether learning using the Project Based Learning model can improve student learning outcomes in chemistry lessons with the subject matter of the nature of Chemistry, and to determine the magnitude of the increase. Classroom Action Research is carried out in 2 cycles, each cycle consisting of stages of planning, action, observation, reflection. The variables used are improvement in learning outcomes including cognitive, and psychomotor values. The instruments used were pretest-posttest, portfolio, observation sheet, and questionnaire questionnaire. Data were analyzed qualitatively descriptive. From the results of the study obtained a picture of students who reached KKM cognitive value as much as 97% with an average value of 82, students who achieved KKM psychomotor value as much as 100% with an average value of 91. There was an increase in the success of teachers in applying the PjBL learning model in the first cycle of 88%, increasing in the second cycle by 97%. The increase in the average activity of students in the first cycle was 82%, increasing in the second cycle by 93%. The average interest of students also increases in the first cycle by 84%, increasing in the second cycle by 92%. Observation of the application of PjBL as a whole shows a very good value of 95. Based on the results of the analysis of the data shows that learning using the Project Based Learning model can improve student learning outcomes of the subject matter of the nature of chemistry. The Project Based Learning learning model is inspiring in developing creative, collaborative and contextual learning methods.   Keywords: Project Based Learning; Improving Learning Outcomes; The Nature of Chemistry